THE RELATIONSHIP WE WANT, AND WE NEED WITH THE ENGAGEMENT OF MEDICAL PROFESSIONALS AND THE RELATIONSHIP WITH THE QUALITY OF CLINICAL SERVICES IN MUHAMMADIYAH HOSPITAL, NORTH SUMATERA - Nora Damayanti; Crismis Novalinda Ginting; Muhammad Faridz Syahrian (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study examines the relationship between intrinsic motivation (We Want) and organizational support (We Need) with professional engagement and their implications for clinical service quality at Muhammadiyah General Hospital, North Sumatra. The study aims to analyze how internal and external factors influence engagement among medical professionals and how this engagement contributes to service quality. A quantitative cross-sectional design was employed involving 32 respondents selected from medical professionals. Data were collected using structured questionnaires and analyzed using descriptive statistics and inferential analysis. The results indicate that intrinsic motivation has a positive and significant relationship with professional engagement, while organizational support demonstrates a stronger influence on engagement levels. Furthermore, professional engagement significantly affects clinical service quality, indicating that engaged medical professionals are more committed, responsive, and adherent to clinical standards. However, findings also reveal that organizational support remains suboptimal, particularly in leadership and communication aspects, which may hinder optimal engagement. Overall, clinical service quality is perceived as good but is primarily driven by individual commitment rather than systemic organizational support. These findings highlight the importance of balancing intrinsic motivation and organizational support to enhance engagement and improve sustainable healthcare service quality.